PREDIKSI PENJUALAN PRODUK PADA SISTEM PENJUALAN POINT OF SALE (POS) DENGAN MENERAPKAN ALGORITMA APRIORI - Hidayat, Taufik; Handayani, Yuni; Mufti, Muhammad Zainul (SKANIKA: Sistem Komputer dan Teknik Informatika, 2023)
The sales transaction data process at Indomaret is good, there is a sales application available that can help in managing sales transactions, but the application used does not support the mobility of management in providing recommendations to buyers to buy more products which will later increase business revenue, even though this data It is very important that it can be accessed online without having to go to an Indomaret outlet or office. The data in the form of analysis of sales data is processed into information used for decision making in order to increase product sales and product innovation. Based on these problems, a sales analysis application program was created using the Apriori Method, and the end result is that an application system is functionally able to generate information to place products or items that consumers are likely to buy simultaneously so as to increase sales as expected so as to be able to increase sales and make it easy for management to make decisions